2013
DOI: 10.1074/jbc.m112.428789
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Neuroprotection from Hypoxia-Ischemia (HI) Brain Injury by Up-regulation of Cytoglobin (CYGB) in a Neonatal Rat Model

Abstract: Background: Potential functions of cytoglobin (CYGB) in neonatal hypoxia-ischemia (HI) brain injury have not been reported. Results: Up-regulation of CYGB reduces HI injury and improves long term cognitive impairment after neonatal HI. Conclusion: CYGB exhibits neuroprotective effects, possibly through antioxidant and antiapoptotic functions as well as by stimulating angiogenesis. Significance: These results provide a novel target for developing a clinically relevant strategy for future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 80 publications
1
39
0
Order By: Relevance
“…The high degree of co-expression with HO-1 is notable as HO-1 is an oxidative stress-inducible protein and enzymatic degradation of heme leads to the production of iron, biliverdin (an antioxidant) and CO (34). Cygb may therefore either be a heme substrate for HO-1 or alternatively, Cygb may, in these HO-1-expressing neurons, regulate the level of the gas-neurontransmitter CO produced by HO-1 in a similar way to that proposed for NO (18,19,21).…”
Section: Discussionmentioning
confidence: 98%
“…The high degree of co-expression with HO-1 is notable as HO-1 is an oxidative stress-inducible protein and enzymatic degradation of heme leads to the production of iron, biliverdin (an antioxidant) and CO (34). Cygb may therefore either be a heme substrate for HO-1 or alternatively, Cygb may, in these HO-1-expressing neurons, regulate the level of the gas-neurontransmitter CO produced by HO-1 in a similar way to that proposed for NO (18,19,21).…”
Section: Discussionmentioning
confidence: 98%
“…Silencing of CYGB in myoblasts is sufficient to induce apoptosis and potentiated the pro-apoptotic effects of hypoxia and oxidants 12 . Modulation of CYGB levels in neonatal rat brains through adenoviral delivery strategies also regulated caspase levels and activation in response to ischemia reperfusion 39 . Our results are reminiscent of the aforementioned study, as indicated by a strong association between the loss of CYGB and caspase-3 activation (Figure 4D).…”
Section: Discussionmentioning
confidence: 99%
“…The globin fold also enables the tissue hemoglobin to serve as either a facilitator of oxygen transport within a cell, a scavenger of nitric oxide, and/or an enzyme with peroxidase activity. Hemoproteins such as cytoglobin (CYGB) neuroglobin (Ngb) have been implicated in mediating neurorestorative responses in models of hypoxia-ischemia and spinal cord trauma [5860]. Although LC-O3PUFAs may also prevent the degradation of these key proteins, the effects of dietary LC-O3PUFAs on this important family needs to be clarified and further characterized.…”
Section: Discussionmentioning
confidence: 99%